PENGELOLAAN SISTEM PENERIMAAN MURID BARU DALAM PERSPEKTIF GOOD SCHOOL GOVERNANCE DI SMP NEGERI 1 PASAWAHAN KABUPATEN PURWAKARTA - Ade Tutty R Rosa; Cynthia Rizki Fitrianti Yahya; Delfi Dwinanda Kardiwan; Fatmawati; Rahmat Hidayat (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The Student Admission System (SPMB) is a strategic public education service that serves as the initial gate for public access to quality education. The implementation of SPMB is not only required to fulfill administrative aspects, but must also reflect the principles of good school governance (Good School Governance/GSG). This study aims to analyze the management of SPMB in the perspective of Good School Governance at SMP Negeri 1 Pasawahan, Purwakarta Regency. This study used a qualitative approach with a case study method. Research informants included the school principal, the SPMB committee, teachers, school operators, the school committee, parents of students, and school supervisors. Data were collected through in-depth interviews, observation, and documentation studies. Data analysis used the Miles, Huberman, and Saldaña model which included data condensation, data presentation, and conclusion drawing. The results showed that the management of SPMB was carried out through the stages of planning, organizing, implementing, and supervising that referred to government regulations. The principle of transparency is realized through the provision of open information to the public. Accountability is demonstrated through reporting and activity documentation mechanisms. Public participation can be seen from the involvement of school committees and parents in the socialization process. Responsiveness is realized through information and complaint services. The effectiveness of SPMB implementation is supported by the use of information technology. Supporting factors include the commitment of school members, technological support, and coordination with the education department, while inhibiting factors include the limited digital literacy of some communities and dynamic regulatory changes. This study recommends strengthening information systems, increasing public digital literacy, and developing an SPMB model based on Good School Governance.